The effect of green marketing and brand image on customer loyalty (study on Starbucks consumers in Medan City) - Harahap, Zelin Auliani Zahra; Harahap, Kartini (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
Various new coffee shops offer cheaper prices. This makes competition in the field of coffee shop business become increasingly tight, even though Starbucks is still very attractive to the public. This study aims to determine the effect of green marketing and brand image on customer loyalty at Starbucks in Medan. The form of research used is quantitative with an associative approach. The population in this study was Starbucks consumers in Medan city, with a sample of 100 respondents. Sampling technique using purposive sampling. Primary Data was obtained through the dissemination of questionnaires via Google Forms. Data analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination test. The results of this study indicate that green marketing and brand image have a significant effect partially or simultaneously on customer loyalty. The correlation coefficient value of 0.668 indicates that there is a fairly close relationship between green marketing and brand image of customer loyalty.